The tram bonus - KACZMAREK, T.; Hafke, H.; Preis, A.; Sandrock, S.; Griefahn, B.; Gjestland, T. (Archives of Acoustics, 2006)
The annoyance of three different sound sources was evaluated in a psychoacoustic experiment. An objective analysis of the stimuli used in the experiment has shown that calculated loudness was responsible for equally annoying pairs of different sound sources. Based on the loudness calculations and annoyance ratings, a "tram bonus" of 3 dB was found in comparison to the bus sound source. In addition, it was found that loudness explains the annoyance results when the LpA max is larger than 74.5 dB(A). With sound levels smaller than 74.5 dB(A) sharpness and roughness contribute to annoyance judgments.